Pemahaman Moratorium Logging Dan Keikutsertaan Masyarakat Dalam Praktek Illegal Logging - Ahmad Humam Hamid (Jurnal Agrisep, 2016)
Illegal logging has become a major scourge in the destruction of forests in Aceh Province. Most community in forest bufferzone have been dependent on this activity. This study aims to analyze the socioeconomic factors that determine for community participation in illegal logging activities. Research has been conducted in six regency in Aceh Province by using surveys and focus group discussions involving investors, workers, and owners of forest processing unit and treader. Research results show that the understanding of forest ecological system, education, the main source of revenue pre-and post-moratorium logging was to determine community participation in the activities of this illegal logging. Therefore needs to be disseminated moratorium logging relation to the understanding of forest ecology, as well as livelyhood empowerment for communities in forest bufferzone.